A gestão do conhecimento como ferramenta potencializadora do programa de pós-graduação em matemática da Universidade Federal da Paraíba - Guedes, Roseli Agapito da Silva (2020)
This research has as general objective to understand the Knowledge Management practices that can contribute to increase the results of the Postgraduate Program in Mathematics, of the Federal University of Paraíba, in the National Evaluation System, of the Coordination for the Improvement of Higher Education Personnel (CAPES). To meet the general objective, we list the following specific objectives: a) to gather information about the Program regarding its academic and administrative structure and functioning, students, managers, teachers' profile, their results from CAPES evaluations, and Knowledge Management practices existing in the Program to understand the way in which the Program seeks, creates, shares and applies its knowledge; b) to identify Knowledge Management (KM) practices within the scope of the Graduate Program in Mathematics that are related to the CAPES National Assessment System; c) develop suggestions for Knowledge Management practices according to the Program's needs, based on the CAPES National Evaluation System, which can contribute to the increase of its results. We opted for a qualitative research, with bibliographic, documentary procedures, and case study, being a descriptive and exploratory research. The relevance of this research is materialized in the face of the need to boost the recognition of the Graduate Program in Mathematics, which seeks, in addition to meeting the requirements imposed by CAPES in the academic field, to strengthen itself in the national and international field. In addition, we understand the need to register actions that allow the exposure of the knowledge of public servants in stricto sensu Graduate Programs at the Federal University of Paraíba, facilitating organizational learning and administrative work development, and can serve as a prior model for these Programs Stricto Sensu postgraduate courses, which may have similar profiles, adapting the results to the situation in which each one is inserted. We analyze the current situation of the studied Program and recognize, within the proposed model of Nonaka and Takeuchi (1997), some tools of Knowledge Management. We developed, as a product of this research, suggestions for Knowledge Management practices based on the post-graduate evaluations carried out by the Coordination for the Improvement of Higher Education Personnel.